2010
DOI: 10.2355/isijinternational.50.702
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Behavior of P2O5 at the Interface between Solid 2CaO·SiO2 and Liquid CaO–SiO2–FeOx–P2O5 Slags Saturated with Solid 5CaO·SiO2·P2O5 at 1 573 K

Abstract: It is important to understand the role of solid phases such as solid CaO or 2CaO · SiO 2 in hot metal dephosphorization. In the present study, the reaction behavior of P 2 O 5 at the interface between solid 2CaO · SiO 2 and liquid CaO-SiO 2 -FeO x -P 2 O 5 slags saturated with solid 5CaO · SiO 2 · P 2 O 5 at 1 573 K was investigated.The result shows that the solid 2CaO · SiO 2 reacts with the liquid phase in the two phase mixture to form the P 2 O 5 condensed phases. Compared with the results by using the homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…[8][9][10][11][12] Based on this topic, various researches have been carried out to reveal the enrichment behavior of phosphorus in recent years. [3][4][5][6][7][13][14][15][16][17][18][19][20] From the perspective of the enrichment mechanism of phosphorus, some explorations have been detected on the distribution of P 2 O 5 between solid solution in 2CaOAESiO 2 -3CaOAEP 2 O 5 (nC 2 S-C 3 P) and liquid solution in the molten slag phase, [13,18] the behavior of phosphorous transfer, [20] and the formation reaction of P-enriched phase, [17] etc. Based on the above investigations, it can be summarized that the solid solution nC 2 S-C 3 P is the main P-enriched phase in the slags.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Based on this topic, various researches have been carried out to reveal the enrichment behavior of phosphorus in recent years. [3][4][5][6][7][13][14][15][16][17][18][19][20] From the perspective of the enrichment mechanism of phosphorus, some explorations have been detected on the distribution of P 2 O 5 between solid solution in 2CaOAESiO 2 -3CaOAEP 2 O 5 (nC 2 S-C 3 P) and liquid solution in the molten slag phase, [13,18] the behavior of phosphorous transfer, [20] and the formation reaction of P-enriched phase, [17] etc. Based on the above investigations, it can be summarized that the solid solution nC 2 S-C 3 P is the main P-enriched phase in the slags.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hasegawa and Iwase 5) and Jeoungkiu IM et al 6) respectively measured the activity of Fe x O and P 2 O 5 in the 3 three-phase regions of CaO-P 2 O 5 -Fe x O system. Tsukihashi et al [7][8][9][10][11] systematically investigated the formation reaction of phosphate compound in multi phase flux and the mass transfer processes between CaO/2CaO·SiO 2 particles and molten slag. In 1982 at the earliest, Ito et al 12) measured the phos-phorus distribution between 2CaO·SiO 2 and CaO-SiO 2 -FeO-Fe 2 O 3 molten slag.…”
Section: )mentioning
confidence: 99%
“…They also studied the phosphorous transfer behavior from CaO-Fe t O-P 2 O 5 (-SiO 2 ) slag to 2CaO•SiO 2 particles 6) and the phosphorous partition between 2CaO•SiO 2 particles and CaO-SiO 2 -Fe t O slag with the similar experimental method. 7) Kitamura et al 8) studied the mass transfer of P 2 10) and Hamano et al 11) studied the reaction mechanisms between solid CaO and CaO-SiO 2 -FeO x -P 2 O 5 slag, and Yang et al [12][13][14][15] studied the reaction mechanisms between 2CaO•SiO 2 and molten CaO-SiO 2 -FeO x -P 2 O 5 slag with the similar experimental method like Suito and Inoue's experiments. Gao et al [16][17][18] studied the phase relationship of the CaO-SiO 2 -FeO-5 mass% P 2 O 5 system by applying the chemical equilibrium method similar to the study reported by Pahlevani et al Takeshita et al 19) measured the free energies of the formation of 2CaO•SiO 2 -3CaO•P 2 O 5 solid solution by applying the gas equilibrium technique.…”
Section: Introductionmentioning
confidence: 99%